Analisis Corporate Governance Characteristics Dalam Mendukung Pengelolaan Risiko Pada PT Bank Pembangunan Daerah Jawa Timur Tbk (Bank Jatim) Cabang Purwosari Pasuruan - Moch Zainul Fanani; Agung Chandra Wahyudi; Ahmad Afandi; Fauzi Irawan; Melyfin Afranza; Ali Muzaky (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The banking industry is the most regulated sector globally due to its strategic role as a financial intermediary and guardian of national economic stability, making the implementation of Good Corporate Governance (GCG) an absolute prerequisite for sound and accountable banking operations. This study aims to evaluate corporate governance (CG) characteristics and their role in supporting risk management at PT Bank Pembangunan Daerah Jawa Timur Tbk (Bank Jatim), Purwosari Pasuruan Branch. A qualitative descriptive approach with a single case study design was employed. Data were collected through in-depth interviews with four key informants (Branch Head, Senior Credit Officer, Head of Operations, and Internal Audit Coordinator), direct observation, and a focused group discussion (FGD) with the branch risk management team, supplemented by document analysis of Bank Jatim’s annual reports, internal audit reports, and risk management policies for 2021–2023. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2014), encompassing data condensation, data display, and conclusion drawing/verification. The findings indicate that Bank Jatim Purwosari Pasuruan Branch has consistently applied the five GCG principles—transparency, accountability, responsibility, independency, and fairness (TARIF)—which proved effective in controlling credit risk through 5C analysis, mitigating operational risk via dual control procedures, and managing compliance risk by adhering to OJK regulations. The branch NPL remained below 2% (averaging 1.76%) during 2021–2023. This study contributes theoretically to the development of an adaptive GCG framework for regional banks in Indonesia, with practical implications including recommendations for strengthening credit decision independence, internalizing risk culture for new employees, and updating the GCG framework to accommodate digital transformation risks.